INSTITUTIONAL FACTORS OF AGRICULTURAL COOPERATIVE SOCIETIES AND INFLUENCES ON ACCESS TO LOAN FROM MICROFINANCE BANKS IN SOUTHWEST NIGERIA (Journal of the Management Sciences, 2025)
The study explores the institutional factors of agricultural cooperative societies and influences on access to loan from microfinance banks in Southwest Nigeria. Specifically, it investigates effect of agricultural cooperatives organizational ability, safety quality, leadership qualities and asset quality on access to loan from microfinance banks. As a survey research, a total of 242 samples comprising Managing Director (MD); Head of Credit (HOC); Head of Operations (HOP); and, the Internal Auditor (IA), were explored from three States in the South west geopolitical zone of Nigeria namely Lagos, Oyo and Ogun States respectively. Applying inferential statistics, the study found out that Organizational abilities such as functional structures, regular meetings, decision-making, objective setting, and conflict management significantly improved access to credit, alongside leaders’ credit experience. Leadership qualities, including education, credit administration experience, and training exposure, as well as asset factors like leadership worth and physical assets, also positively influenced loan access. The study therefore recommends among others that ii.         Improved financial planning and robust business plans could help cooperatives present stronger cases for full loan amounts, potentially reducing the gap between requested and granted funds. It also recommended that enhancing risk management frameworks could allow microfinance banks to approve higher loan amounts with confidence, thus better supporting agricultural projects.
Keywords: Loan Request; Access From Microfinance Banks; Agricultural Cooperatives; Safety Quality; Leadership Qualities; Asset Quality